The quality and reliability of short videos about hypertension on TikTok: a cross-sectional study - Jiabei Wu; Guiping Wu; Xiaowen Che; Jinli Guo (Scientific Reports)
Abstract Hypertension is a major global health risk, and social media platforms like TikTok play an increasing role in public health communication. This study evaluates the quality of hypertension-related videos on TikTok and examines the relationship between content quality and user engagement. A systematic keyword search identified hypertension-related videos published before February 25, 2025. After applying exclusion criteria, 139 videos were analyzed. Video quality was assessed using the Journal of the American Medical Association (JAMA) benchmark criteria, the Global Quality Scale (GQS), and the modified DISCERN (mDISCERN) instrument. Engagement metrics (likes, comments, shares, and collections) were recorded, and Spearman’s correlation and linear regression analyses explored associations between quality and engagement. These videos accumulated 7190634 likes, 3608023 collections, 247602 comments, and 3252697 shares. Most (85.6%, n = 119) were uploaded by health professionals. The most common JAMA score was 2 (74.8%), while the mean GQS score was 3, with 36.7% of videos receiving this rating. The mDISCERN score was most frequently 2 (71.2%). Video duration correlated with JAMA (β = 0.235, p < 0.05), mDISCERN (β = 0.190, p < 0.05), and GQS scores (β = 0.410, p < 0.001). Likes also correlated with JAMA (β = 0.661, p < 0.001), mDISCERN (β = 0.500, p < 0.05), and GQS scores (β = 0.815, p < 0.001). Comments negatively affected GQS scores (β = -0.574, p < 0.05). TikTok is a valuable platform for hypertension education, but content quality is moderate. Extending video duration, improving rigor, and enhancing review mechanisms may improve hypertension-related health communication.